Proactivity inventory development for senior high school students - Masnurrima Heriansyah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2020)
Understanding of students' attitudes in responding, taking initiative and responsibility is needed by the guidance and counseling teacher so that they can optimally develop themselves. This research aims to produce proactivity inventory for senior high school students. The research subjects were senior high school students in Samarinda. The research design used was mixed method design. Inventory validity was conducted through the stage of expert assessment and item-test correlation using Pearson product-moment correlation coefficient analysis, while reliability was obtained by calculating Alpha coefficient through Cronbach's alpha reliability analysis. The results of research generated 48 inventory items that were used to measure proactivity consisting of aspects of choosing response, ability to take initiative and take responsibility. The research conclusion generated proactivity inventory consisting of 48 items including positive and negative statements. Research implications can help the implementation of guidance and counseling services in senior high school.